Tourist Information Centre in Cluj-Napoca, Romania - Pop, Cornelia; Cosma, Smaranda; Negrusa, Adina (Univerzita Pardubice, 2006)
This paper intend to present the authors’ point of view regarding the creation of a tourist information centre in the home town, Cluj-Napoca. The present situation regarding the tourist information centres at Romania’s level could and should be improved and Cluj-Napoca is among those cities which need such a centre. The structure of this centre and the involvement of interested stakeholders would be presented below, along with the importance of such a centre for Cluj-Napoca.
Keywords: Tourism; information centre; tourist destination; development